Synthesis and characterization of aromatic copolyesters containing siloxane linkages in the polymer backbone - Waghmare, P. B.; Idage, Susheela B.; Menon, Shamal K.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A new series of aromatic copolyesters containing siloxane linkages were prepared by the melt polymerization of bisphenol A (BPA) with eugenol end-capped siloxane (EuSi), diphenyl terephthalate (DPT), and diphenyl isoplithalate (DPI) in varying ratio in the temperature range 220-290 degrees C under reduced pressure in the presence of dibutyl tin dilaurate (DBTL) catalyst. The siloxane copolyesters prepared were characterized by FTIR, H-1-NMR spectroscopy, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The effect of incorporation of eugenol end-capped siloxane was studied on the properties of BPA/DPI/DPT copolyesters. The glass-transition temperature of copolyester was decreased from 184 to 70 degrees C by incorporation of 20% of eugenol endcapped siloxane. All copolyesters were found to be soluble in commonly used aprotic polar solvents and had film-forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: aromatic copolyesters; Bisphenol A; diphenyl isophthalate; diphenyl terephthalate; eugenol end-capped siloxane; melt polymerization